Infant out-of-Hospital Mortality and Ways to Reduce It - Daria S. Kryuchko; Irina I. Ryumina; Vera V. Chelysheva; Ekaterina V. Sokolova; Elena N. Baibarina (Вопросы современной педиатрии, 2019)
Infant mortality is one of the key indicators of demography, characterizing not only the state of health and a social standard of living in a country, region, city, but also an indicator of the level of state development. In recent years there has been a steady downward trend in infant mortality. To the greatest extent, this trend is driven by improved quality of medical care. However, death of children outside healthcare facilities is the least controlled in the structure of infant mortality. The article considers the main causes of deaths of children under the age of one year outside healthcare facilities in the Russian Federation in 2017, presents data of the world and national statistics, analyses possible solutions to the problem.